Penerapan Platform Digital Learn and Growth Dalam Meningkatkan Kompetensi Teacherpreneurship Guru Belajar Jepara - Hamidaturrohmah; Mahendra, Danang; Saefudin, Ahmad; Nahar, Afifatun; Pratama, Adrian Dico (JOM, 2024)
Teachers wield significant influence over the quality of education. To enhance this influence, they must possess competent skills, including teacherpreneurship. This study aims to assess the efficacy of the digital learning platform, "Learn and Grow with Jepara Teachers," in bolstering the teacherpreneurship capabilities of educators in Jepara. Employing a descriptive quantitative approach via survey methodology, the research analyzes the platform's impact. Survey results are statistically analyzed and subjected to data reduction. The findings reveal the positive effects of the digital platform on Jepara teachers' teacherpreneurship competencies. Specifically, 94% strongly agree and 6% agree regarding enhanced technical skills. Regarding conceptual skills, 86% strongly agree and 14% agree. Human skills saw 89% strongly agree and 11% agree. These results indicate a notable improvement in teacherpreneurship competencies among Jepara educators, encompassing heightened knowledge, conceptual insight, skill refinement, and internal motivation towards entrepreneurship.